2015
DOI: 10.1128/iai.02587-14
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component System GrvRS (EtaRS) Regulates ace Expression in Enterococcus faecalis OG1RF

Abstract: e Expression of ace (adhesin to collagen of Enterococcus faecalis), encoding a virulence factor in endocarditis and urinary tract infection models, has been shown to increase under certain conditions, such as in the presence of serum, bile salts, urine, and collagen and at 46°C. However, the mechanism of ace/Ace regulation under different conditions is still unknown. In this study, we identified a two-component regulatory system GrvRS as the main regulator of ace expression under these stress conditions. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, these studies were carried out in the unrelated strain JH2-2. A more recent study (38) indicated that the deletion of the ers gene did not affect ace expression in OG1RF; instead, these investigators found that GvrR, a response regulator protein encoded by the gvrRS two-component genes, activated ace transcription. They also found that GvrR activation of ace occurred in organisms grown at 46°C and in the presence of serum, whereas all our experiments employed cultures grown at 37°C in the absence of serum; since several previous studies focused on protein expression, the temperature effects could be posttranscriptional.…”
Section: Discussionmentioning
confidence: 97%
“…However, these studies were carried out in the unrelated strain JH2-2. A more recent study (38) indicated that the deletion of the ers gene did not affect ace expression in OG1RF; instead, these investigators found that GvrR, a response regulator protein encoded by the gvrRS two-component genes, activated ace transcription. They also found that GvrR activation of ace occurred in organisms grown at 46°C and in the presence of serum, whereas all our experiments employed cultures grown at 37°C in the absence of serum; since several previous studies focused on protein expression, the temperature effects could be posttranscriptional.…”
Section: Discussionmentioning
confidence: 97%
“…Ace is regulated by the GrvRS two-component regulatory system and, accordingly, gvrR mutants are attenuated for biofilm formation in vitro and for virulence in a murine model of ascending UTI [140]. The ArgR family transcription factor AhrC is important for early biofilm formation in vitro, and ahrC mutans are significantly attenuated for biofilm growth on catheters as well as for bladder and kidney colonization during CAUTI [141].…”
Section: Urinary Tract Infection Caused By Enterococcimentioning
confidence: 99%
“…Additional E. faecalis surface proteins that contribute to urovirulence in animal models include the collagen adhesin Ace and the enterococcal fibronectin binding protein EfbA [ 28 , 138 , 139 ]. Ace is regulated by the GrvRS two-component regulatory system and, accordingly, gvrR mutants are attenuated for biofilm formation in vitro and for virulence in a murine model of ascending UTI [ 140 ]. The ArgR family transcription factor AhrC is important for early biofilm formation in vitro, and ahrC mutans are significantly attenuated for biofilm growth on catheters as well as for bladder and kidney colonization during CAUTI [ 141 ].…”
Section: E Faecalis Uti Virulence Factorsmentioning
confidence: 99%